Предмет: Математика, автор: AnnaKolja

Помогите пожалуйста!

Приложения:

Ответы

Автор ответа: Miroslava227
1

Ответ:

21. 2

22. 1

23. 2

24. 4

25. 2

26. 4

27. 4

Пошаговое объяснение:

21.

 {( \frac{ {x}^{ -  \frac{1}{2} } \times  {x}^{ \frac{1}{3} }  }{ \sqrt{x} \times  {x}^{ -  \frac{1}{3} }  } )}^{ \frac{3}{4} }  =  {( {x}^{ -  \frac{1}{2}  -  \frac{1}{2} }  \times  {x}^{ \frac{1}{3}  +  \frac{1}{3} } )}^{ \frac{3}{4} }  =  \\  =   {( {x}^{ - 1 +  \frac{2}{3} } )}^{ \frac{3}{4} }  =  {( {x}^{ -  \frac{1}{3} } )}^{ \frac{3}{4} }  =  \\  =  {x}^{ -  \frac{1}{4} }  =  \\  \\  =  {(0.0625)}^{ -  \frac{1}{4} }    =  \sqrt[4]{ \frac{10000}{625} }  =  \\  =  \frac{10}{5}  = 2

22.

 \frac{ {3}^{ \frac{1}{2} }  \times  {2}^{ \frac{1}{2} } }{ \sqrt[4]{36} }  =  \frac{ {6}^{ \frac{1}{2} } }{ \sqrt[4]{ {6}^{2} } }  =  \frac{ {6}^{ \frac{1}{2} } }{ {6}^{ \frac{1}{2} } }  = 1 \\

23.

 \frac{ {a}^{ \frac{2}{3} } - 16 }{ {a}^{ \frac{1}{3} } - 4 }  -  { a}^{ \frac{1}{3} }  =  \frac{ {a}^{ \frac{2}{3} } - 16 -  {a}^{ \frac{1}{3} }( {a}^{ \frac{1}{3} }  - 4)  }{ {a}^{ \frac{1}{3} }  - 4}  =  \\  =  \frac{ {a}^{ \frac{2}{3} } - 16 -  {a}^{ \frac{2}{3} }   + 4 {a}^{ \frac{1}{3} } }{ {a}^{ \frac{1}{3} } - 4 }  =  \frac{4( {a}^{ \frac{1}{3} }  - 4)}{ {a}^{ \frac{1}{3} } - 4 }   = 4

24.

 {a}^{ \frac{1}{4} }  \div  {a}^{ - 0.75}  =  {a}^{ \frac{1}{4}  - ( -  \frac{3}{4} )}  =  {a}^{1}  = a

25.

 {a}^{ - 1 \frac{1}{2} }  \div  {a}^{ -  \frac{6}{7} }  =  {a}^{ -  \frac{3}{2} +  \frac{6}{7}  }  =  {a}^{ \frac{ - 21 + 12}{14} }  =  \\  =  {a}^{ -  \frac{9}{14} }

26.

 {9}^{3p}  \times  {3}^{ -  \frac{1}{p} }  =  {3}^{6p}  \times  {3}^{ -  \frac{1}{p} }  =  {3}^{6p -  \frac{1}{p} }  =  \\  \\  =  {3}^{3 - 2}  =  {3}^{1}  = 3

27.

 {3}^{ - 6p}  \times  \frac{1}{ {3}^{ - 4p} }  =   {3}^{ - 6p}  \times  {3}^{4p}  =  {3}^{ - 2p}   = \\  \\  =  {3}^{4}  = 81

Похожие вопросы